STANDARISASI KURSUS: ANTARA KEBUTUHAN DAN KESULITAN MENETAPKAN BENCHMARK - Supriyono Supriyono (Jurnal Ilmiah Visi, 2007)
Course institutions are one kind of well-known non-formal education unit in Indonesia. Its role and contribution in the development of national system and the development of human resources can not be neglected. The amount of course institutions fluctuates overtime; however, it can be assured that the amount stays significantly fulfilling the learning need of the people. In 2002, the recorded amount of course institution is 22,510, but it decreased up to 11,745 in 2005. Those institutions provide 167 types of courses and trainings, which can be categorized into several subjects of study. According to the Government Regulation of Number 19 in 2005 on the National Standard of Education, course institutions need to have standardization. Different from the formal education (school) standard which is more systematical and homogeneous, the standardization for course institutions faces obstacles related to the minimum criteria of several components because of the wide variability and heterogeneity on its types, scopes, and levels.